Assessment of the safety of use of portable machine tools - Monika Nowak; Agnieszka Terelak-Tymczyna (Scientific Journal of the Military University of Land Forces, 2018)
The article presents safety issues related to on-site machining with the use of portable machine tools. Their advantage is the possibility of machining elements at places in which they are used. This especially refers to large-size constructions, welded elements and any items whose disassembly is technically difficult. The authors present tasks performed by the operators of portable machining equipment, working conditions, construction and characteristic features of portable machine tools on the example of a portable boring machine, milling machine and flange facing machine. The presented characteristics can influence the safety of work with these machines. The information given in the article were used to asses risk at the position of a portable machine tool operator. The assessment was conducted using the Risk Score method taking into account four stages of using portable machine tools, i.e. transport, assembly/disassembly, machining and maintenance. The result of the conducted risk analysis is the proposal of possible risk reducing actions. Due to the specificity of the operation of portable machine tools which significantly impedes the development of a machine tool which would be safe in and of itself, the proposed actions refer mainly to organisational solutions. The work presents also the thesis that it is possible to decrease the risk at this position thanks to the use of numerical control in a portable machine tool. Such a solution may reduce exposure to some identified threats. The issue is presented on the example of a prototype of a portable flange facing machine developed in the Institute of Mechanical Technology ZUT in Szczecin.